An AHP Algorithm for an Effective ERP Type Selection Based on the African Context. Issue 1 (5th December 2017) - Armand, Manga Tobie; Roger, Atsa Etoundi
Abstract: The Literature reports many studies on ERP implementation in many African countries and points out the difficulties faced by these countries in the sustainable management of the selected solution. The data in this domain reveals that most of the projects are abandoned in the early stages of their life cycle. Moreover, for ERP solutions that have been put in place, most of them are used with serious difficulties which usually pushed the organisation to abandon the system, and implement a legacy one that meets the requirements related to the human capital and financial constraints. The present paper contributes to the ERP literature within the African context by proposing a model for ERP type decision making. The model is based on the AHP (Analytic Hierarchy Process) method and use contextual dimensions to sustain the decision making related to what is the best suited ERP type for an African organisation.